E-077 Protein expression of intra-arterial blood distal and proximal to thrombus during mechanical thrombectomy. (4th August 2020) - Maglinger, B; Frank, J; McLouth, C; Trout, A; Roberts, J; Grupke, S; Turchan-Cholewo, J; Stowe, A; Fraser, J; Pennypacker, K
Abstract : Introduction: Since 2015, mechanical thrombectomy is the standard treatment for emergent large vessel occlusion ischemic stroke. The Blood and Clot Thrombectomy Registry and Collaboration (BACTRAC) protocol (clinicaltrials.gov NCT03153683 ) utilizes thrombectomy to isolate intracranial (i.e. distal to thrombus) arterial blood, systemic arterial blood, and the thrombus itself. We set out to investigate how the protein expression of a patient's intracranial blood during ischemic stroke compares to the protein expression of their systemic arterial blood in order to better understand and treat stroke. Methods: Intracranial and systemic plasma samples from n=25 subjects were randomized and sent for cardiometabolic and inflammatory proteomic analyses at Olink Proteomics (Olink Proteomics, Boston, MA). Olink provides a Normalized Protein eXpression (NPX), a unit that is in log2 scale which allows for individual protein analysis across a sample set. The intracranial versus systemic fold change in NPX was calculated by subtracting the systemic NPX (NPXs ) from the intracranial NPX (NPXi ). In order to determine which proteins had the most significant changes, a series of 184 paired t-tests were performed, one for each of the 92 cardiometabolic and 92 inflammatory proteins. Data analysis was performed using SAS software version 9.4 (SAS Institute Inc., Cary, N.C.). Results: 83 proteins with significantly different expression levels between intracranial and systemic blood were identified and all 83 exhibited lower expression in the intracranial blood. For the cardiometabolic panel, the 5 most significant fold changes were: prolyl endopeptidase (FAP) at -0.26 (p<0.0001), phospholipid transfer protein (PLTP) at -0.26 (p=0.0005), uromodulin (UMOD) at -0.14 (p=0.002), fetuin-B (FETUB) at -0.31 (p=0.002), and ficolin-2 (FCN2) at -0.46 (p=0.005). For the inflammatory panel, the 5 most significant fold changes were: C-C motif chemokine 19 (CCL19) at -0.51 (p<0.0001), C-C motif chemokine 20 (CCL20) at -0.40 (p<0.0001), fibroblast growth factor 21 (FGF21) at -0.37 (p=0.0002), transforming growth factor alpha (TGF-a) at -0.28 (p=0.0002), and C-C motif chemokine (CCL23) at -0.43 (p=0.0003). Discussion: We have, for the first time, evaluated proteomic changes in the intravascular space of a cerebral infarct in-progress in human subjects. Interestingly, for all significant proteins, expression levels were lower in the intracranial blood compared to systemic. The most significantly changed proteins may represent specific responses occurring at the time of ischemia. For example, changes in proteins such as SOD1 and FGF21 may play a neuroprotective role in response to ischemia. Chemokines such as CCL23 are related to the Th2 autoimmune response and may become important in the repurposing of FDA approved drugs for future therapeutic studies. Variations in proteases, ischemia timeline, patient co-morbidities, reperfusion injury, and basal levels of systemic protein expression may all contribute to the finding of lower intracranial protein expression. Future studies will focus on parsing out the influence of these potential factors as well as on relationships between proteomic changes and patient comorbidities, sex, infarct severity and functional recovery. Proteomic data reported here may provide a scientific springboard for identifying clinically relevant biomarkers, as well as targets for much-needed neuroprotective and neuroreparative pharmacotherapies. Disclosures: B. Maglinger: None. J. Frank: None. C. McLouth: None. A. Trout: None. J. Roberts: None. S. Grupke: None. J. Turchan-Cholewo: None. A. Stowe: 4; C; Cerelux, LLC. J. Fraser: 1; C; AHA, University of Kentucky. 2; C; Stream Biomedical, Medtronic, Penumbra. 4; C; Cerelux, LLC; Fawkes Biotechnology. K. Pennypacker: 4; C; Cerelux, LLC.